# Maharashtra Board 11th Maths Solutions Chapter 3 Permutations and Combination Ex 3.2

Balbharti Maharashtra State Board 11th Maths Book Solutions Pdf Chapter 3 Permutations and Combination Ex 3.2 Questions and Answers.

## Maharashtra State Board 11th Maths Solutions Chapter 3 Permutations and Combination Ex 3.2

Question 1.
Evaluate:
(i) 8!
Solution:
8!
= 8 × 7 × 6 × 5 × 4 × 3 × 2 × 1
= 40320

(ii) 10!
Solution:
10!
= 10 × 9 × 8 × 7 × 6 × 5 × 4 × 3 × 2 × 1
= 3628800

(iii) 10! – 6!
Solution:
10! – 6!
= 10 × 9 × 8 × 7 × 6! – 6!
= 6! (10 × 9 × 8 × 7 – 1)
= 6! (5040 – 1)
= 6 × 5 × 4 × 3 × 2 × 1 × 5039
= 3628080

(iv) (10 – 6)!
Solution:
(10 – 6)!
= 4!
= 4 × 3 × 2 × 1
= 24

Question 2.
Compute:
(i) $$\frac{12 !}{6 !}$$
Solution:
$$\frac{12 !}{6 !}=\frac{12 \times 11 \times 10 \times 9 \times 8 \times 7 \times 6 !}{6 !}$$
= 12 × 11 × 10 × 9 × 8 × 7
= 665280

(ii) $$\left(\frac{12}{6}\right) !$$
Solution:
$$\left(\frac{12}{6}\right) !$$
= 2!
= 2 × 1
= 2

(iii) (3 × 2)!
Solution:
(3 × 2)!
= 6!
= 6 × 5 × 4 × 3 × 2 × 1
= 720

(iv) 3! × 2!
Solution:
3! × 2!
= 3 × 2 × 1 × 2 × 1
= 12

(v) $$\frac{9 !}{3 ! 6 !}$$
Solution:
$$\frac{9 !}{3 ! 6 !}=\frac{9 \times 8 \times 7 \times 6 !}{(3 \times 2 \times 1) \times 6 !}=84$$

(vi) $$\frac{6 !-4 !}{4 !}$$
Solution:
$$\frac{6 !-4 !}{4 !}=\frac{6 \times 5 \times 4 !-4 !}{4 !}=\frac{4 !(6 \times 5-1)}{4 !}=29$$

(vii) $$\frac{8 !}{6 !-4 !}$$
Solution:
$$\frac{8 !}{6 !-4 !}=\frac{8 \times 7 \times 6 \times 5 \times 4 !}{6 \times 5 \times 4 !-4 !}$$
= $$\frac{8 \times 7 \times 6 \times 5 \times 4 !}{4 !(6 \times 5-1)}$$
= $$\frac{1680}{29}$$
= 57.93

(viii) $$\frac{8 !}{(6-4) !}$$
Solution:
$$\frac{8 !}{(6-4) !}=\frac{8 !}{2 !}$$
= $$\frac{8 \times 7 \times 6 \times 5 \times 4 \times 3 \times 2 !}{2 !}$$
= 20160

Question 3.
Write in terms of factorials
(i) 5 × 6 × 7 × 8 × 9 × 10
Solution:
5 × 6 × 7 × 8 × 9 × 10 = 10 × 9 × 8 × 7 × 6 × 5
Multiplying and dividing by 4!, we get
= $$\frac{10 \times 9 \times 8 \times 7 \times 6 \times 5 \times 4 !}{4 !}$$
= $$\frac{10 \times 9 \times 8 \times 7 \times 6 \times 5 \times 4 \times 3 \times 2 \times 1}{4 !}$$
= $$\frac{10 !}{4 !}$$

(ii) 3 × 6 × 9 × 12 × 15
Solution:
3 × 6 × 9 × 12 × 15
= 3 × (3 × 2) × (3 × 3) × (3 × 4) × (3 × 5)
= (35) (5 × 4 × 3 × 2 × 1)
= 35 (5!)

(iii) 6 × 7 × 8 × 9
Solution:
6 × 7 × 8 × 9 = 9 × 8 × 7 × 6
Multiplying and dividing by 5!, we get
= $$\frac{9 \times 8 \times 7 \times 6 \times 5 !}{5 !}$$
= $$\frac{9 \times 8 \times 7 \times 6 \times 5 \times 4 \times 3 \times 2 \times 1}{5 !}$$
= $$\frac{9 !}{5 !}$$

(iv) 5 × 10 × 15 × 20
Solution:
5 × 10 × 15 × 20
= (5 × 1) × (5 × 2) × (5 × 3) × (5 × 4)
= (54) (4 × 3 × 2 × 1)
= (54) (4!)

Question 4.
Evaluate: $$\frac{n !}{r !(n-r) !}$$ for
(i) n = 8, r = 6
(ii) n = 12, r = 12
(iii) n = 15, r = 10
(iv) n = 15, r = 8
Solution:

Question 5.
Find n, if
(i) $$\frac{n}{8 !}=\frac{3}{6 !}+\frac{1 !}{4 !}$$
Solution:

(ii) $$\frac{n}{6 !}=\frac{4}{8 !}+\frac{3}{6 !}$$
Solution:

(iii) $$\frac{1 !}{n !}=\frac{1 !}{4 !}-\frac{4}{5 !}$$
Solution:

(iv) (n + 1)! = 42 × (n -1)!
Solution:
(n + 1)! = 42(n – 1)!
∴ (n + 1) n (n – 1)! = 42(n – 1)!
∴ n2 + n = 42
∴ n2 + n – 42 = 0
∴ (n + 7)(n – 6) = 0
∴ n = -7 or n = 6
But n ≠ -7 as n ∈ N
∴ n = 6

(v) (n + 3)! = 110 × (n + 1)!
Solution:
(n + 3)! = (110) (n + 1)!
∴ (n + 3)(n + 2)(n + 1)! = 110(n + 1)!
∴ (n + 3) (n + 2) = (11) (10)
Comparing on both sides, we get
n + 3 = 11
∴ n = 8

Question 6.
Find n, if:
(i) $$\frac{(17-n) !}{(14-n) !}=5 !$$
Solution:

∴ (17 – n) (16 – n) (15 – n) = 6 × 5 × 4
Comparing on both sides, we get
17 – n = 6
∴ n = 11

(ii) $$\frac{(15-n) !}{(13-n) !}=12$$
Solution:
$$\frac{(15-n) !}{(13-n) !}=12$$
∴ $$\frac{(15-n)(14-n)(13-n) !}{(13-n) !}=12$$
∴ (15 – n) (14 – n) = 4 × 3
Comparing on both sides, we get
∴ 15 – n = 4
∴ n = 11

(iii) $$\frac{n !}{3 !(n-3) !}: \frac{n !}{5 !(n-5) !}=5: 3$$
Solution:

∴ 12 = (n – 3)(n – 4)
(n – 3)(n – 4) = 4 × 3
Comparing on both sides, we get
n – 3 = 4
∴ n = 7

(iv) $$\frac{n !}{3 !(n-3) !}: \frac{n !}{5 !(n-7) !}=1: 6$$
Solution:

∴ 120 = (n – 3)(n – 4) (n – 5)(n – 6)
∴ (n – 3)(n – 4) (n – 5)(n – 6) = 5 × 4 × 3 × 2
Comparing on both sides, we get
n – 3 = 5
∴ n = 8

(v) $$\frac{(2 n) !}{7 !(2 n-7) !}: \frac{n !}{4 !(n-4) !}=24: 1$$
Solution:

(2n – 1)(2n – 3)(2n – 5) = $$\frac{24 \times 7 \times 6 \times 5}{16}$$
∴ (2n – 1)(2n – 3)(2n – 5) = 9 × 7 × 5
Comparing on both sides. We get
∴ 2n – 1 = 9
∴ n = 5

Question 7.
Show that $$\frac{n !}{r !(n-r) !}+\frac{n !}{(r-1) !(n-r+1) !}=\frac{(n+1) !}{r !(n-r+1) !}$$
Solution:

Question 8.
Show that $$\frac{9 !}{3 ! 6 !}+\frac{9 !}{4 ! 5 !}=\frac{10 !}{4 ! 6 !}$$
Solution:

Question 9.
Show that $$\frac{(2 n) !}{n !}$$ = 2n (2n – 1)(2n – 3)…5.3.1
Solution:

Question 10.
Simplify
(i) $$\frac{(2 n+2) !}{(2 n) !}$$
Solution:

(ii) $$\frac{(n+3) !}{\left(n^{2}-4\right)(n+1) !}$$
Solution:

(iii) $$\frac{1}{n !}-\frac{1}{(n-1) !}-\frac{1}{(n-2) !}$$
Solution:

(iv) n[n! + (n – 1)!] + n2(n – 1)! + (n + 1)!
Solution:

(v) $$\frac{n+2}{n !}-\frac{3 n+1}{(n+1) !}$$
Solution:

(vi) $$\frac{1}{(n-1) !}+\frac{1-n}{(n+1) !}$$
Solution:

(vii) $$\frac{1}{n !}-\frac{3}{(n+1) !}-\frac{n^{2}-4}{(n+2) !}$$
Solution:

(viii) $$\frac{n^{2}-9}{(n+3) !}+\frac{6}{(n+2) !}-\frac{1}{(n+1) !}$$
Solution: